CODE MIXING ANALYSIS IN HIGH SCHOOL STUDENTS’ CONVERSATION - Masda Surti Simatupang; Ni Komang Sunari (Lingua, 2021)
Many people can speak more than one language and can use both languages with similar abilities. They can talk in one language and mix it with another language. This phenomenon exists mainly among teenagers. This paper aims to analyze code-mixing in Indonesian conversation among students at SMA 99 Jakarta. The code mixing used by these students was analyzed based on the forms of each English utterance in the Indonesian language. The methodology used in this study was descriptive qualitative with 15 participants. The data were collected through an online interview conducted using the Zoom video call instrument. During the video call at Zoom, the writers asked questions using the informal Indonesian language. Some of the questions concern favorite movies, activities during the Covid-19 pandemic, applications for listening to songs, and vacation. Those conversations were recorded and stored as data for analysis. Based on the recording, there are 49 English words mixed in their Indonesian conversation. All data were analyzed into three forms of code-mixing: words, phrases, and sentences. The results showed that students at SMA 99 Jakarta indeed used English mixing code in their conversation in informal Indonesian.